WORKING ON TEXT AS A WAY TO ACTIVATE AND IMPROVE THE RUSSIAN SPEECH OF STUDENTS FROM NON-LANGUAGE DEPARTMENTS - Yuldashev Aziz Uzgenovich (Western European Studies, 2025)
This article focuses on working with text as a way to activate and improve students' Russian speech
Keywords: Speech; activation; improvement